Q: What is 2x plus 4y-5x plus 3y?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

2x-11

4(2x + 3y)(2x + 3y)

the simplest form of 5x + 3y +2x - 6y is 7x-3y

-2x plus 3y equals 1

6x plus 3y minus 2x plus 5y equals 4x plus 8y.

Related questions

6x + 3y + 6y - 2x = (6x - 2x) + (3y + 6y) = 4x + 9y

2x-11

4(2x + 3y)(2x + 3y)

the simplest form of 5x + 3y +2x - 6y is 7x-3y

2x + 3y + 4x + 9y = 2x + 4x + 3y + 9y = 6x + 12y which can be simplified to 6(x + 2y)

2x plus 3y

Collect like terms: 2x + 3y + 3y - 5 - 6 2x + 6y - 11

-2x plus 3y equals 1

6x plus 3y minus 2x plus 5y equals 4x plus 8y.

10x - 3y + 2x - 4y =(10x + 2x) + (-3y - 4y) =12x - 7y

2x + 3y - x + 5y combine the like terms 2x - x + 3y +5y simple arithmetic x + 8y

2x2 + 6xy = 2x (x + 3y)